(untitled) (Northern International Medical College Journal, 2022)
Background : Dengue is the most important arthropod transmitted human viral disease and constitutes an important worldwide health problem including Bangladesh. Although children are the usual victim of dengue infection, there is paucity of published data regarding its clinical profile and outcome in children in our country. Objective: Now, in case of children Dengue fever is a common cause of acute febrile illness in our country, but the magnitude of it is quite unknown. Therefore, this study aims to find out the common clinical manifestations, the early warning signs and the outcome of dengue fever in different age group of children. Materials and Methods: The present study was conducted in the Popular Medical College Hospital, Dhanmondi, Dhaka (a tertiary care private hospital) between July to September of 2019 on children of dengue fever from 1year up to 15 years of age. It is a retrospective observational study. Results: A total of 58 cases were enrolled. The common clinical presentations included fever (100%), arthralgia (81.9%), cough/ coryza (17.2%), headache/retro orbital pain (3.4%), and rash (10.3%). The common early warning signs at the time of admission were persistent vomiting (41.4%), severe abdominal pain (27.6%), Hepatomegaly (6.9%). Regarding clinical course, in Dengue fever (DF), Dengue Hemorrhagic fever (DHF) and Dengue Shock Syndrome (DSS) total 36 (62%), 14 (24.2%), 8 (13.8%) children are affected respectively. Conclusion: The clinical manifestations of dengue fever are like other viral infections, but the disease severity is more in dengue. Thus, if we able to find out the more common clinical findings of dengue fever, it would help us in early diagnosis and early initiation of appropriate treatment. In this study we found that the most common clinical symptom was fever, found in 100% cases, arthralgia in 81.9%, cough/ coryza in 17.2%, headache / retro orbital pain in 10.3% and rash in 3.4% cases. Among the 58 cases 36 (62%) were diagnosed as DF, 14 (24.2%) as DHF and 8 (13.8%) as DSS and no death was occurred. Northern International Medical College Journal Vol. 12 No.1 July 2020, Page 499-502